Effectiveness of Sublingual Immunotherapy in the Treatment of HDM-Induced Nasobronchial Allergies: A 3-Year Randomized Case-Control Study From Kashmir - Baba, Shahid M.; Rasool, Roohi; Gull, Ayaz; Qureshi, Taha A.; Beigh, Afaq H.; Qadri, Qurteeba; Shah, Zafar A. (Frontiers in Immunology, 2021)
Allergen immunotherapy (AIT) is the only disease-modifying treatment for allergic disorders that induces immunological tolerance through administration of specific allergens. Studies on AIT for subcutaneous route are in abundance; however, the efficacy of AIT in tablet form through sublingual route has not been well elucidated. The present prospective, parallel-group, controlled study sought to compare the efficacy of sublingual immunotherapy (SLIT) tablets with pharmacotherapy (PT) in 332 house dust mite (HDM)-specific allergic asthma and/or rhinitis patients over a period of 3 years. Patients were followed up for a 6-month run-in period and then randomly stratified as those who would receive SLIT, SLIT in addition to PT (SLIT+PT), and PT alone. AIT was administered in the form of sublingual tablets. Symptom and medication scores were measured every 3 months. In vitro evaluation of serum total and HDM specific immunoglobulin E (HDM sIgE) levels was carried out every 3 months, whereas in vivo skin prick test was performed annually for 3 years. Our study demonstrated sustained clinical improvement, reduction in inhaled corticosteroid (ICS) dose and duration as well as prevention from development of neosensitization to other aero allergens in HDM-allergic asthmatics and/or rhinitis patients treated with 3 years SLIT. Despite a remarkable clinical improvement with AIT, we observed that SLIT did not significantly change the skin reactivity to HDM at 3 years and there was no significant change in the ratio of serum total and HDM sIgE. Given the immune and disease modifying effects of AIT in allergic diseases, the present study supports the notion of its sublingual mode being an effective long-term immunomodulator in HDM-sensitized nasobronchial allergies.